Implant-supported mandibular overdentures: a retrospective case series study in a daily dental practice - Shebrina F. Abdoel; Stephanie S. Haagedoorn; Gerry M. Raghoebar; Henny J. A. Meijer (SpringerOpen, 2021)
Abstract Background Evaluation of dental implant treatment is mostly based on studies with well-controlled study groups treated within a university-based setting. There are no long-term observational practice-based studies known on implant-supported overdentures. The present retrospective study deals with implant survival, peri-implant hard and soft tissue health, surgical and prosthetic aftercare, and satisfaction of patients treated with an implant-supported mandibular overdenture in a daily dental practice. Materials and methods Within the years 2006 till 2015, 295 patients were treated with two, three, or four implants for mandibular overdenture treatment in a daily dental practice in Zaandam, The Netherlands. Outcome parameters were scored at a routine yearly inspection including implant loss, plaque index, gingival index, bleeding index, presence of calculus, probing depth, and satisfaction with implant-supported overdenture. Radiographic analysis was performed to assess peri-implant bone changes. Surgical and prosthetic aftercare was obtained from the medical record. Results A total of 133 patients were seen for an evaluation visit (mean follow-up 51.2 months). Cumulative implant survival rate in the 2-implant group, 3-implant group, and 4-implant group was 100%, 99.1%, and 97.8% respectively, with a mean peri-implant bone loss of 0.53 mm, 0.61 mm, and 0.40 mm. Patients' satisfaction was high in all groups. Conclusion It was demonstrated, within the limitations of this study, that patients, who were treated with an implant-supported mandibular overdenture in a daily dental practice, experienced a high cumulative implant survival rate and a good peri-implant health, and were very satisfied. Trial registration Netherlands Trial Register, NL8867 . Registered 15 September 2020-retrospectively registered.